MENINGKATKAN PERKEMBANGAN SENI ANAK MENGGUNAKAN MEDIA SMART HAFIZ DI PAUD AIZA KABUPATEN KEPAHIANG - Sysva Nurwita (Early Childhood Research and Practice, 2020)
The purpose of this study was to determine the development of children's art using Smart Hafiz media. Early childhood has unique characteristics, each of which is different from one another. Education plays an important role at this time. This is because early childhood is a golden age that cannot be repeated a second time. Early childhood education is children aged 0-6 years, early childhood education has a very important role in developing children's personalities and preparing children to enter further education levels. The method used was PTK with data sources, namely 15 students of Paud AIZA Kepahiang Regency. The results obtained were the development of children's art developed very well with a score of 84.3%. The development of children's art is supported by the media used, namely Smart Hafiz media which has a lot of interesting content so that children's learning activities are not monotonous and the development of children's art is increased.